Strategi Pengadaan Bahan Pustaka Tercetak Di Perpustakaan Umum Daerah Kabupaten Lima Puluh Kota - Wahyuni, Sri; Fitrianis, Fitrianis (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The primary issue in this thesis is how to acquire printed library materials from the Regional Public Library of Fifty Cities Regency, as well as the issues and solutions to those issues. The reason for this conversation is to figure out the system for the acquirement of printed library materials at the Provincial Public Library of Fifty Urban areas Rule, to figure out the issues in the acquisition of printed library materials at the Local Public Library of Fifty Urban areas Regime and to figure out arrangements about the obtainment of printed library materials at the Territorial Public Library of Fifty Urban communities Regime. This sort of examination utilized by the creator is a kind of unmistakable methodology research with a subjective technique. Purposive and snowball sampling methods are utilized in this study. This study makes use of methods like observation, interviewing, and documentation with media like books, pens, mobile phones, and other things that can be made into things, which are examples of research instruments that can be thought of as auxiliary tools. The study's findings indicate that the Regional Public Library of Fifty Cities Regency's procurement strategy for printed library materials must be enhanced to meet the needs of patrons and keep up with the times. There are two methods for securing printed library materials at the Provincial Public Library of Fifty Urban communities Rule, to be specific the buy technique and the present/gift/award strategy. The procedure for receiving library materials is carried out by procurement at the Fifty Cities Regency Regional Public Library. This includes carefully examining the library materials received and their cover letters, matching the library materials received with the results of the survey recapping user needs, setting aside and repairing library materials with damaged orders, defects in the library material processing room, signing receipts or invoices to the sender of library materials, marking the ownership of library materials with a stamp of the inventory of the Fifty Cities Regency Public Library, making a report of The limited budget available and collections that are difficult to locate or difficult to purchase in a store present a challenge when purchasing library materials.